A Surface-Integral Model for Log P-OW - Kramer, Christian; Beck, Bernd; Clark, Timothy (Journal of Chemical Information and Modeling, 2010)
Log P-OW, the negative logarithm of the octanol-water partition coefficient, is omnipresent in computational drug design. Here, we present a surface-integral model for calculating log P-OW. The model is based on local properties calculated using AM1 semiempirical molecular orbital theory. These are the molecular electrostatic potential (MEP), local ionization energy (IEL), local electron affinity (EA(L)), local hardness (HARD), local polarizability (POL), and the local field normal to the surface (FN). We have developed a new scheme to calculate a local hydrophobicity based on binning the range of local surface properties instead of using polynomial expansions of the base terms. The model has been trained using similar to 9500 compounds available from the literature. It was validated oil similar to 1350 compounds froth the literature and all in-house validation set of 768 compounds from Boehringer-Ingelheim. The model performs similarly to or slightly better than the best commercially available models. We also introduce a model based purely on conformationally rigid compounds that performs well for flexible compounds if the Boltzmann weighted predictions for the different conformers are used. This is the first 3D QSPR model based on such a large databasis that is able to benefit from using conformational ensembles.